The impact of geomagnetic storms on the occurrences of earthquakes from 1994 to 2017 using the generalized linear mixed models / Nur Anisah Mohamed@A. Rahman ... [et al.] - Mohamed@A. Rahman, Nur Anisah; Ismail, Nor Hidayah; Abdul Majid, Nur Saadah; Ahmad, Nazhatulshima (2021)
This study is to investigate the impact of geoeffective solar events and geomagnetic storms on the occurrences of earthquakes from 1994 to 2017 in a statistical perspective where the data for the geomagnetic Ap index and shallow worldwide earthquakes were used. The Ap index is obtained from the Helmholtz-Centre Postdam – GFZ German Research Centre for Geosciences, and the earthquake events are from the United States Geological Survey (USGS) earthquake catalogue. We introduced the Generalised Linear Mixed Models (GLMM) to investigate a dynamic relationship between high geomagnetic storms with earthquake frequency across time. The GLMM is suitable for correlated and nonlinearly distributed data. It can be observed that there was an increase in earthquake frequency following the extreme value of the Ap index.